X3D Moving Grid Methods for Semiconductor Applications. Issue 1 (1998) - Kuprat, Andrew; Cartwright, David; Gammel, J. Tinka; George, Denise; Kendrick, Brian; Kilcrease, David; Trease, Harold; Walker, Robert
Abstract : The Los Alamos 3D grid toolbox handles grid maintenance chores and provides access to a sophisticated set of optimization algorithms for unstructured grids. The application of these tools to semiconductor problems is illustrated in three examples: grain growth, topographic deposition and electrostatics. These examples demonstrate adaptive smoothing, front tracking, and automatic, adaptive refinement/derefinement.